Pengaruh Role Playing terhadap Keterampilan Berbicara Peserta didik di MI/SD - Reflina, Reflina; Siregar, Sulthon Zulkarnain; Zannurain, M Fauzan; Wardani, Putri; Wirdia, Indah Aini; Harahap, Muhammad Rijal Hasan (Universitas Muhammadiyah Enrekang, 2024)
The aim of this research was to determine: 1) Implementation of role playing in class V of SD Al-Ittihadiyah, 2) speaking skills of class V students of SD Al-Ittihadiya, 3) the influence of role playing on the speaking skills of class V students of SD Al-Ittihadiyah. The method in this research uses quantitative research, the type of research used is quasi-experimental. The population at this time is 38 people, all of them are class V students at Al-Ittihadiyah Elementary School for the 2023/2024 academic year. The sampling technique used in this research is total sampling. The research instruments and tools used to collect data in this research are observation. The data analysis techniques used are Descriptive Statistical Data Analysis and Inferential Statistical Data Analysis. Based on the results of data analysis, it was found that 1) The speaking skills of fifth grade students at Al-Ittihadiyah Elementary School showed that the average speaking skills of students in the control class who did not receive treatment received a score of 65.26, while those who received treatment using Role Playing in the experimental class received a score of 76. .58, 2) The application of role playing in Class V of Al-Ittihadiyah Elementary School shows an increase according to the results of data analysis in the average level of students' speaking skills after implementing Role 76.58. This average value shows that the students' speaking ability after implementing role playing is higher than the average value of students' speaking ability before being given treatment. 3) The effect of role playing on the speaking skills of fifth grade students at SD Al-Ittihadiyah is 65.26 with a standard deviation of 10.603. This means that there is an increase in the average student's speaking ability. The average value before being given treatment was 56.84, with a standard deviation of 13.664, and the value after being given treatment was 76.58 and a standard deviation of 6.882. Finally, based on the results of the independent t test, the Sig (2 tail) value was 0.000 < 0.005. Accepted, this means that there is an influence between the role playing learning model and students' speaking skills in Indonesian language learning at SD Al-Itiihadiyah T.A 2023/2024.